Pengelolaan Sumberdaya Alam Dalam Menyanggah Perekonomian Warga Desa Cibeusi - Novi Ardilah; Wegi Lesmana; Rifa Nurfalah; N. Syaadiah; Sinta Nurlela; Afif Nurseha (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
Cibeusi Village is a village located in the Ciater sub-district, Subang district, West Java province, Cibeusi village is nicknamed the tourist village because of the many tours that are still maintained and have been recognized by the local government. With a fairly fertile soil condition, Cibeusi village is one of the best black rice-producing villages, besides that there are many types of vegetables, palm sugar, capolaga and others, becoming a source of community income so that the residents' economy increases with the rich natural resources of Cibeusi village. The purpose of this study is to describe and analyze Natural Resource Management in Refuting the Economy of Cibeusi Villagers. This research uses qualitative research. The data was collected by interview and observation methods. The research results obtained include: (1) a lot of tourism potential such as Curug Cibareubeuy, Curug Ciangin, Muara Guava and others. (2) the potential of abundant natural resources in Cibeusi village such as black rice, palm sugar, vegetables and many others. (3) In Cibeusi village there are several plants that are managed by craftsmen into valuable items including imocraft wood, uyun plants, gunz bamboo and so on.